Bioaccessibility and bioavailability of biofortified food and food products: Current evidence - Huey, Samantha L.; Mehta, Neel H.; Konieczynski, Elsa M.; Bhargava, Arini; Friesen, Valerie M.; Boy, Erick; Krisher, Jesse T.; Mbuya, Mduduzi; Monterrosa, Eva C.; Nyangaresi, Annette M.; Mehta, Saurabh (Informa UK Limited, 2024)
Biofortification increases micronutrient content in staple crops through conventional breeding, agronomic methods, or genetic engineering. Bioaccessibility is a prerequisite for a nutrient to fulfill a biological function, e.g., to be bioavailable. The objective of this systematic review is to examine the bioavailability (and bioaccessibility as a proxy via in vitro and animal models) of the target micronutrients enriched in conventionally biofortified crops that have undergone post-harvest storage and/or processing, which has not been systematically reviewed previously, to our knowledge. We searched for articles indexed in MEDLINE, Agricola, AgEcon, and Center for Agriculture and Biosciences International databases, organizational websites, and hand-searched studies’ reference lists to identify 18 studies reporting on bioaccessibility and 58 studies on bioavailability. Conventionally bred biofortified crops overall had higher bioaccessibility and bioavailability than their conventional counterparts, which generally provide more absorbed micronutrient on a fixed ration basis. However, these estimates depended on exact cultivar, processing method, context (crop measured alone or as part of a composite meal), and experimental method used. Measuring bioaccessibility and bioavailability of target micronutrients in biofortified and conventional foods is critical to optimize nutrient availability and absorption, ultimately to improve programs targeting micronutrient deficiency.